THE DEVELOPMENT OF THE EPIDEMIC PROCESS OF PARASITES IN YOUNG CHILDREN (Journal of Science-Innovative Research in Uzbekistan, 2024)
Parasitic disease - the development of painful symptoms as a result of the life of a helminth or protozoa in the human body. The main factor in the survival and spread of parasites is their unusually high reproductive ability, as well as constantly improving mechanisms of adaptation to living in the human body